Influence of Dietary Supplementation of Peppermint (Mentha piperita) and Lemongrass (Cymbopogon citratus) Essential Oils on Health Biomarkers in CrossbredCalves - Sarma, Gautami; Palod, Jyoti; Arya, Anita; Kumar, Shive; Sharma, Sanjay; Sharma, R. K.; Singh, S. K .; Gangwar, Sumit (Indian Journal of Animal Nutrition, 2025)
The present study evaluated the effects of dietary supplementation with Mentha piperita essential oil (MPEO) and Cymbopogon citratus essential oil (CCEO) on the hematological profile, serum biochemical parameters, and blood antioxidant status in crossbred calves. 18 crossbred calves (Sahiwal × Holstein Friesian), aged between two weeks and three months, were allocated into three groups: T0 (control), T1 (MPEO at 0.2% of calf starter), and T2 (CCEO at 0.2% of calf starter). The study was conducted over 90 days, with blood samples collected at monthly intervals: 0, 30th, 60th and 90th day for study of haemato-biochemical parameters while at 45th and 90th day for antioxidant parameters . Hematological analysis showed a significant (P<0.05) increase in total erythrocyte count (TEC) and packed cell volume (PCV) in the T2 group, while eosinophil counts were significantly (P<0.05) reduced in both T1 and T2 groups of calves. No significant treatment effects were observed on total leukocyte count (TLC), differential leukocyte counts, or platelet counts. Biochemical analysis revealed significant reductions in serum urea (P<0.01) levels and alanine aminotransferase (P<0.05) in T1 and T2 group of calves. Lipid profile results revealed significant (P<0.05) reductions in triglycerides, total cholesterol (P<0.01), LDL, and VLDL in Cymbopogon citratus essential oil group and an increase in HDL cholesterol in both Mentha piperita essential oil (MPEO) and Cymbopogon citratus essential oil groups. As regards antioxidant parameters, lipid peroxidase (LPO) was significantly (P<0.05) reduced, and superoxide dismutase (SOD) activity was significantly (P<0.01) increased in the Cymbopogon citratus essential oil group of calves. The results suggest that Cymbopogon citratus essential oil supplementation positively influences hematological parameters, lipid metabolism, and antioxidant status, with potential benefits for calf health and performance. Further studies are recommended to explore the long-term effects of these essential oils.